Worldwide Prevalence of Intimate Partner Violence in Pregnancy. A Systematic Review and Meta-Analysis - Rosario M. Román-Gálvez; Rosario M. Román-Gálvez; Sandra Martín-Peláez; Sandra Martín-Peláez; Borja M. Fernández-Félix; Borja M. Fernández-Félix; Javier Zamora; Javier Zamora; Khalid S. Khan; Khalid S. Khan; Aurora Bueno-Cavanillas; Aurora Bueno-Cavanillas; et al. (Frontiers Media S.A., 2021)
Background: Intimate partner violence (IPV) affects outcomes of mothers and their offspring. This systematic review collated the worldwide literature on the prevalence rates of different types of IPV in pregnancy.Methods: Two reviewers independently identified cross sectional and cohort studies of IPV prevalence in pregnancy in online databases (PubMed, WOS and Scopus), selected and extracted data [participants' country, study quality, measurement tool (validation and purpose) and rates of IPV in pregnancy]. We considered a high quality study if it had a prospective design, an adequate sampling method, a sample size estimation, a response rate > 90%, a contemporary ascertainment of IPV in the index pregnancy, and a well-developed detailed IPV tool. We performed random effects meta-analysis and explored reasons for heterogeneity of rates.Results: One hundred fifty-five studies were included, of which 44 (28%) met two-thirds of the quality criteria. Worldwide prevalence of physical (126 studies, 220,462 participants), psychological (113 studies, 189,630 participants) and sexual (98 studies, 155,324 participants) IPV in pregnancy was 9.2% (95% CI 7.7-11.1%, I2 95.9%), 18.7% (15.1-22.9%, I2 98.2%), 5.5% (4.0-7.5%, I2 93.4%), respectively. Where several types of IPV were reported combined, the prevalence of any kind of IPV (118 studies, 124,838 participants) was 25.0% (20.3, 30.5%, I2 98.6%). IPV rates varied within and between continents, being the highest in Africa and the lowest in Europe (p < 0.001). Rates also varied according to measurement purpose, being higher for diagnosis than for screening, in physical (p = 0.022) and sexual (p = 0.014) IPV.Conclusions: IPV prevalence in pregnancy varies across countries, with one-quarter of mothers exposed on average globally. Routine systematic antenatal detection should be applied worldwide.Systematic Review Registration: identifier: CRD42020176131.